Pharmacist‐physician collaborative care model and time to goal blood pressure in the uninsured population. Issue 1 (13th December 2017) - Dixon, Dave L.; Sisson, Evan M.; Parod, Eric D.; Van Tassell, Benjamin W.; Nadpara, Pramit A.; Carl, Daniel; W. Dow, Alan
Abstract : Pharmacist‐physician collaborative practice models (PPCPMs) improve blood pressure (BP) control, but their effect on time to goal BP is unknown. This retrospective cohort study evaluated the impact of a PPCPM on time to goal BP compared with usual care using data from existing medical records in uninsured patients with hypertension. The primary outcome was time from the initial visit to the first follow‐up visit with a BP <140/90 mm Hg. The study included 377 patients (259 = PPCPM; 118 = usual care). Median time to BP goal was 36 days vs 259 days in the PPCPM and usual care cohorts, respectively ( P  < .001). At 12 months, BP control was 81% and 44% in the PPCPM and usual care cohorts, respectively ( P  < .001) and therapeutic inertia was lower in the PPCPM cohort (27.6%) compared with usual care (43.7%) ( P  < .0001). Collaborative models involving pharmacists should be considered to improve BP control in high‐risk populations.